Evaluation of Medication-Related Challenges in Hypertensive Patients: A Comprehensive Assessment at Community Based Medical College, Bangladesh (CBMC,B) Hospital (Community Based Medical Journal, 2025)
A cross-sectional, observational study was carried out at Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and September of 2023, to assess the proportion and nature of drug therapy problems, the regimen management of hypertension, and the associated risks among hypertensive patients. A total of 120 hypertensive patients willingly participated and responded to a structured questionnaire. Patient data include demographic characteristics, medications, clinical parameters, lifestyle factors, and drug therapy issues. The study included an equal distribution of males and females, with most patients aged 49-58 years (29.2%). Telmisartan (62.5%) and amlodipine (50.0%) were the most commonly prescribed medications. Among drug therapy problems (DTPs), need for monitoring (35%) and potential drug interactions (31.67%) were found most significant. Diabetes mellitus (37.50%) and chronic kidney disease (25.83%) were main comorbidities. Stress (50%) and unhealthy diet (49.17%) emerged as leading risk factors, while polypharmacy (55%) and comorbidities (53.33%) in patients emerged as main clinical challenges. This study suggests that medication review processes need to be well structured, resources required for improving the patients’ knowledge about hypertension and its treatments are necessary for healthcare organizations in the country and monitoring activities ought to be conducted from time to time to review the management of hypertension.  CBMJ 2025 January: Vol. 14 No. 01 P: 128-133